PSIKOEDUKASI: DAMPAK KECANDUAN GADGET ORANG TUA TERHADAP PERKEMBANGAN ANAK - Ella Setiani; Eva Sartika; Raihana Raihana (Kreasi: Jurnal Pengabdian Masyarakat, 2022)
Currently, many parents experience addiction or are addicted to playing gadgets both when they are with their children and when they are not playing with their children. Children feel like they have lost many beautiful moments with their parents, because of the neglect made by their parents. The aim of carrying out this service is to provide understanding and additional knowledge to parents about the impact of gadget addiction experienced by parents on children's development. The method used in this research is the lecture method. The result of this community service is in the form of increasing parental understanding of the impacts caused if parents continue to play with gadgets without paying attention to the child's development, such as the child's social and emotional development and also the child's language development.